2017
DOI: 10.1002/hbm.23711
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of dynamic functional connectivity from brain grey matter and white matter for MCI classification

Abstract: Brain functional connectivity (FC) extracted from resting-state fMRI (RS-fMRI) has become a popular approach for diagnosing various neurodegenerative diseases, including Alzheimer's disease (AD) and its prodromal stage, mild cognitive impairment (MCI). Current studies mainly construct the FC networks between grey matter (GM) regions of the brain based on temporal co-variations of the blood oxygenation level-dependent (BOLD) signals, which reflects the synchronized neural activities. However, it was rarely inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 92 publications
(118 reference statements)
1
124
0
Order By: Relevance
“…The integrated feature information from multi-modality images can provide more comprehensive details, which can be utilized by the proposed framework for better classification performance. We will also incorporate alternative machine learning techniques in the fields of image segmentation (Zhang et al, 2016, 2017b), image super-resolution (Zhang et al, 2017c) and classification (Zhang et al, 2017d; Chen et al, 2017), and seek further performance improvements in PD diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…The integrated feature information from multi-modality images can provide more comprehensive details, which can be utilized by the proposed framework for better classification performance. We will also incorporate alternative machine learning techniques in the fields of image segmentation (Zhang et al, 2016, 2017b), image super-resolution (Zhang et al, 2017c) and classification (Zhang et al, 2017d; Chen et al, 2017), and seek further performance improvements in PD diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that machine learning using structural and functional brain imaging features classify healthy elderly and MCI groups with higher accuracy [46-48]. Additionally, several studies have classified the MCI group with high accuracy by evaluating dynamic FC, considering the complex and dynamic interaction patterns among brain regions [49, 50]. In this regard, further studies, which focus on dynamic FC of the ReHo-based seeds and investigate group differences, will need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…When the enhanced FCTs are obtained, they are non-rigidly registered to the MNI-152 space using SPM [40]. We then generate 359 fiber probability maps based on the method described in [41, 42] [43]. Each template is a probability WM mask indicating inter-subject consistent connections between any pair of Automated Anatomical labeling (AAL) brain regions, generated using the data of 500 subjects in HCP dataset.…”
Section: Methodsmentioning
confidence: 99%